1980
DOI: 10.1002/jpln.19801430506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonate in clay fraction on fixation of zinc

Abstract: The results indicate that CaCO3 in the clay fraction of Egytian soils has a greater affinity for Zn than silicate clay. Moreover, in the presence of carbonate, Zn was retained more tightly to form complexes hard to be extracted and, thus, relatively unavailable for plant uptake. Therefore, CaCO, plays an important role in zinc deficiency which is commonly found in calcareous soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The percentage of clay also increased compared to the studied sites' soils, while the proportion of silt and sand decreased in these locations, which is due to the role of carbonate minerals in linking minute clay with silt and sand, or the presence of clay in clusters size of silt and sand coated with carbonate minerals, making it one of the largest (figure 3). This result was confirmed by Osman et al (1980), who found a change in the texture after removing the carbonate minerals from all study soils.…”
Section: Soil Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…The percentage of clay also increased compared to the studied sites' soils, while the proportion of silt and sand decreased in these locations, which is due to the role of carbonate minerals in linking minute clay with silt and sand, or the presence of clay in clusters size of silt and sand coated with carbonate minerals, making it one of the largest (figure 3). This result was confirmed by Osman et al (1980), who found a change in the texture after removing the carbonate minerals from all study soils.…”
Section: Soil Propertiessupporting
confidence: 83%
“…Several processes control the behavior of Zn Q/I parameters in soils, including adsorptiondesorption and precipitation-dissolution (Pasricha et al, 1987). Some physical and chemical properties of the soil affect the Zn adsorption process, such as the amount of clay, organic matter content, total active carbonate content (Osman et al, 1980), and increased soil pH. This research aims to study the behavior of zinc adsorption via Q/I parameters such as zinc potential buffering capacity, labile zinc, zinc activity ratio, Gapon Coefficient, and exchangeable zinc-free energy in order to evaluate zinc bioavailability in these soils using ten calcareous soils samples from Northern Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that CaCO 3 in soils led to Zn precipitation as ZnCO 3 . Osman et al (1980) demonstrated that CaCO 3 plays an important role in Zn deficiency which is found in Egypt's calcareous soils. Morera et al (2002) found that the availability of Zn was remarkably low in soil with high carbonate content.…”
Section: Effect Of Organic Wastes and Incubation Time On Dynamics Of mentioning
confidence: 99%